Arrangement of Legal Policy-Based Land Administration Digitalization in Gobah Village, Kampar Regency, Riau: Penataan Digitalisasi Administrasi Pertanahan Berbasis Kebijakan Hukum di Desa Gobah Kabupaten Kampar Riau - Ardiansyah Ardiansyah; Efendi Ibnu Susilo; Panca Setyo Prihatin; Pahmi Amri; M. Rafi (Universitas Lancang Kuning, 2023)
In its development, the tendency of an agrarian society has shown how important the land sector is for rural communities to develop and improve their economy through the land sector. Thus, this PKM activity is important because the idea of ​​a legal policy regarding the digitization of land administration must be well organized to accelerate the development process and as a basis for the legal settlement process. The method of implementing this PKM activity has several steps such as identifying initial problems through observation and interviews, socializing the arrangement of digitizing land administration based on legal policies, carrying out FGDs, and evaluating PKM activities systematically. The results of the PKM activity in Gobah Village showed that this activity was carried out in three main sessions, namely registration of participants and opening of the event, resource persons giving presentations, and FGD sessions with local communities. Then this activity can be said to have been carried out well, but there are still some notes that need to be carried out regularly to improve the quality of land data.